PERUBAHAN POLA PIKIR ORANG BAJO TERHADAP MINAT MENGIKUTI PENDIDIKAN TINGGI DI DESA BONTU-BONTU KECAMATAN TOWEA KABUPATEN MUNA - Ilham Yasan, Teguh; Taena, La; Ali Basri, La Ode (Universitas Halu Oleo, 2021)
The objectives of this study is to identify and analyze the change in the mindset of the Bajo people towards their interest in higher education in the village of Bontu-Bontu. The method used in this study is a descriptive method with a qualitative approach. The instrument of this research is the researcher himself as the key instrument and the interview guide as a supporting instrument. Data collection techniques in this study are, Observation, Interview and Documentation. The results showed that there was a change in the mindset of the Bajo people towards their interest in attending higher education in Bontu-Bontu Village. Data show that the Bajo people in the village of Bontu-Bontu in the early 2000s did not attend higher education. At this time education is not considered important. The Bajo people in Bontu-Bontu Village are seen from their way of thinking and their attitude towards higher education is very apathetic and indifferent. Then now there has been a change in the Bajo people in the village of Bontu-Bontu, they have started to use higher education as a means to improve the quality of human resources and change a much better future in order to compete with outsiders. To date, there have been 13 Bajo people in Bontu-Bontu Village who have completed higher education. Data for 2018-2021 shows that there are 13 people who are currently attending higher education.Keywords: Mindset Changging, Intereset In Higher Educaton, Bajo People.